Analysis of The Savonius Type Vertical Axis Wind Turbine Prototype - Nur Hayati; Sudarsono; Panji PJ (IPTEK The Journal for Technology and Science, 2026)
Wind is a term for moving air. Considering that fossil fuel sources are dwindling, wind has the potential to be used as a source of electricity. A generating system is needed to convert wind into energy. A turbine or often called a windmill is a device that can utilize wind power by converting mechanical energy into electrical energy. Wind turbines are classified as horizontal axis turbines or vertical axis turbines depending on the direction of rotation of the rotor. One of the vertical type turbines is the Savonius turbine. This turbine is very suitable for application in Indonesia because it has several advantages, including being able to rotate at relatively low wind speeds, being able to receive wind from all directions, as well as ease and low construction costs. This research aims to analyze the Savonius wind turbine prototype with 2, 3 and 4 blades. The turbine blade material used is PLA (Polylactic Acid), which is a biodegradable thermoplastic made from cane sugar or cornstarch which is environmentally friendly. Blade dimensions 100 mm x 102 mm x 2 mm. Data collection was carried out by testing at wind speeds of 3 m/s and 4 m/s. Wind speed is kept constant through the windtunnel. Experimental results show that the number of rotor rotations is inversely proportional to the number of turbine blades. Likewise for the turbine power coefficient. The turbine with 2 blades has the best performance compared to the other two turbines.